Influencing Urban Planning Policy: An Exploration from the Perspective of Public Health. Issue 1 (2nd January 2018) - Kent, Jennifer L.; Harris, Patrick; Sainsbury, Peter; Baum, Fran; McCue, Peter; Thompson, Susan
Abstract: Human health requires the proper development and management of places through urban planning. This paper demonstrates how concerns for human health can become explicit matters for consideration in urban planning policy systems. Taking advantage of a rare opportunity to examine the policy development process, we combine a realist analysis, with a new institutional policy approach, to study a case of planning system review in Australia. These insights are useful for practitioners presented with similar opportunities for legislative influence. We also demonstrate the way this approach can be used in future research to develop rich insights into the forces at play in positioning health as explicitly related to urban governance.